2004
DOI: 10.1212/01.wnl.0000124465.20878.84
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pergolide in treatment of restless legs syndrome

Abstract: Pergolide substantially improves periodic limb movement measures and subjective sleep disturbance associated with restless legs syndrome. Low-dose pergolide was well tolerated and maintained its efficacy in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…The improvement in RLS symptoms occurred as early as 6 weeks, similar to the time course of common pharmaceutical treatments, 12,22 and the reduction in RLS symptoms was maintained throughout the 3 month intervention period. Additionally, the improvement in RLS symptoms appeared to show a ceiling effect at 6 weeks, with no further significant improvement occurring.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The improvement in RLS symptoms occurred as early as 6 weeks, similar to the time course of common pharmaceutical treatments, 12,22 and the reduction in RLS symptoms was maintained throughout the 3 month intervention period. Additionally, the improvement in RLS symptoms appeared to show a ceiling effect at 6 weeks, with no further significant improvement occurring.…”
Section: Discussionsupporting
confidence: 57%
“…Again, this may be similar to pharmacological treatment, as in trials of pharmaceuticals for RLS, the response to treatment appears to be greatest at 6 to 12 weeks, with further treatment not providing additional reduction in symptoms. 22,23 Future studies are needed to further address the effects of exercise on the symptoms of RLS. The current study results are promising, but larger studies are necessary before exercise is routinely prescribed for RLS.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were attenuated but remained robust in the ITT analysis (Table 3; P Ͻ 0.0001). In a sensitivity analysis restricted to the 25 participants from the per-protocol cohort with baseline moderate-to-severe RLS, SDHD resulted in an even larger 8-to 9-point decrease in the mean IRLS score at 4 and 12 months (23 (21,25) versus 14 (9,20) versus 13 (8,18); P Ͻ 0.001). The ITT analysis yielded similar results among the 57 participants with baseline moderate-to-severe RLS, with a significant 6-to 7-point improvement over the same time period (P Ͻ 0.001).…”
Section: Effect Of Sdhd On Rlsmentioning
confidence: 97%
“…Nine of the 10 items investigate two dimensions of RLS severity, symptoms (six items), and symptoms effect (three items). This self-administered instrument was developed and validated by the IRLS Study Group (18,20) and has been used to test the efficacy of drugs developed for treatment of RLS (21,22). Responses are graded from 0 to 4, with a higher score reflecting higher severity.…”
Section: Assessment Of Rls and Symptoms Severitymentioning
confidence: 99%
“…A long-term study revealed no serious adverse effects of pergolide, over 48 weeks, at doses from 0.5 to 0.75 mg 62 . However, although effective in the treatment of RLS, pergolide was withdrawn from the U.S. market due to the risk of cardiac valvulopathy (derived from the experience over use of ergot in the treatment of Parkinson's disease and prolactinomas and endorsed by study recente 63 .…”
Section: Major Da Ergot Pergolidementioning
confidence: 96%